Michael Rakowitz I'm good at love, I'm good at hate, it's in between I freeze - Downey, Anthony ca. 20. Jh (Sternberg Press, 2019)
Michael Rakowitz's 'I'm good at love, I'm good at hate, it's in between I freeze' charts the historical context and aftermath of a concert that never happened. In 2009, the inimitable Leonard Cohen was scheduled to perform at the Ramallah Cultural Palace in Palestine. (The title of the book is a line from Cohen's ?A Thousand Kisses Deep.?) As a result of the cultural boycott of Israel, the concert was canceled, but the story, as Rakowitz's work demonstrates, did not end there. Conjoining the cultural histories of Palestine and Israel and the ethical dilemmas faced by performers and artists in the face of political intransigence, this volume brings to light the research that went into this multifaceted work and plots the future arc of its yet-to-be completed trajectory
Keywords: Rakowitz, Michael -- 1973-